TRANSFORMASI INOVASI MODEL BISNIS PADA UMKM BATIK PASCA PANDEMI COVID 19 - Azhar, Ratih Mukti; Evanthi, Ayundha (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The pandemic phenomenon had a significant impact on small and medium-sized enterprises, compelling them to respond to the situation. Business Model Innovation (BMI) represents an innovation model suitable for the sustainability of small and medium-sized enterprises, particularly as the local SME situation deteriorated during the first two years of the COVID-19 pandemic, specifically in 2020-2021. The reconfiguration of business models has emerged as one of the alternatives for SMEs to overcome these challenges. The business model concept enables Small and Medium Enterprises (SMEs) to tackle dynamic business challenges. In reality, the alteration of Business Models (BMs) in SMEs varies across different organizations. This research aims to provide insights into the changes in BMs for SMEs following the pandemic, specifically within the batik industry, through the Integrated Marketing Communications (IMC) approach applied to various case studies. The method used in this research is descriptive qualitative through case studies with case selection using a purposive sampling approach, which is the MSME of the Batik Industry. The results of this study offer empirical information about the Business Model Innovation (BMI) of SMEs during the pandemic, which can serve as a foundation for further research in BMI, particularly concerning SMEs. Keywords: Business Model Innovation; SMEs; Batik; Pandemic